2020
DOI: 10.1038/s41398-020-01046-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial electron transport proteins and increased complement mediators in plasma neural-derived exosomes of early psychosis

Abstract: Potentially neurotoxic systems involved in traumatic and degenerative diseases of the brain were assessed in acute psychosis. Astrocyte-derived exosomes (ADEs) and neuron-derived exosomes (NDEs) were immunoprecipitated from plasma of ten untreated first-episode psychotics (FPs) and ten matched normal controls (Cs). Neural mitochondrial electron transport and complement proteins were extracted, quantified by ELISAs and normalized with levels of CD81 exosome marker. Levels of subunits 1 and 6 of NADH-ubiquinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…Extracellular vesicle marker CD81-normalized levels of representative proteins in mitochondrial electron transport complexes I and III, but not IV, had been shown to be significantly lower in ADEVs and NDEVs of FP patients than ctls. 11 Existing data relevant to these levels of electron transport complexes suggested that ROS production would, therefore, be higher and ATP generation lower in mitochondria of both types of CNS cells of FP patients than ctls. 16 CD81normalized enzymatic activity of ATP synthase (complex V) was significantly higher for ctl ADEVs than NDEVs and ATP synthase activity in NDEVs of FP patients was not significantly different than that in ctls (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular vesicle marker CD81-normalized levels of representative proteins in mitochondrial electron transport complexes I and III, but not IV, had been shown to be significantly lower in ADEVs and NDEVs of FP patients than ctls. 11 Existing data relevant to these levels of electron transport complexes suggested that ROS production would, therefore, be higher and ATP generation lower in mitochondria of both types of CNS cells of FP patients than ctls. 16 CD81normalized enzymatic activity of ATP synthase (complex V) was significantly higher for ctl ADEVs than NDEVs and ATP synthase activity in NDEVs of FP patients was not significantly different than that in ctls (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the neural exosome protein abnormalities previously identified in this study group of ten FP patients had suggested neuroinflammation, altered neural mitochondrial electron/proton transport and decreased neural survival mechanisms. 11 Blood was obtained at the same time of day from all participants without fasting.…”
Section: Research Participant Selection and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to biomarkers reflecting amyloidosis, tauopathy, neurodegeneration, and insulin resistance [ 6 , 8 , 9 , 10 , 11 ], EVs and NDEVs contain mitochondrial cargo, including mitochondrial RNAs [ 12 ], that may be used to investigate mitochondrial abnormalities in AD. The study of abnormalities of mitochondrial oxidative phosphorylation and ROS elimination in living humans has recently become possible through assessing plasma NDEV levels of ETC proteins and SOD1, a pursuit initially undertaken in relation to psychosis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Goetzl et al further found a severe reduction in MFN2 and CYPD proteins in the NDE of patients with schizophrenia, suggesting the impairment of mitochondria in the disease [ 126 ]. They collected astrocyte-derived exosomes (ADE) to determine the upregulation of complement proteins; this suggests that complement abnormalities occur in astrocytes in schizophrenia [ 127 ]. Currently, there are limited reports on the collection of microglia-derived exosomes (MDE) [ 128 ] because microglia largely share the surface marker with peripheral macrophages.…”
Section: Potential Diagnosis/medication For Schizophrenia Based On Microglia–synapse Interactionmentioning
confidence: 99%